MASKING STRATEGIES TO AVOID THE BOAR TAINT IN MEAT PRODUCTS - Županjac, Miloš; Šojić, Branislav; Ikonić, Predrag (Journal on Processing and Energy in Agriculture, 2023)
Surgery to castrate male pigs can be substituted by the manufacture of “entire males”. However, the meat of whole male animals may have unpleasant sexual odor, i.e. - boar taint. The purpose of this paper was to demonstrate how to use masking techniques on meat that has a noticeable boar taint during the processing stage. Smoke has frequently been implicated as a method for hiding boar taint in many types of meat products. Meat items may be smoked naturally using a traditional method or artificially using liquid smoke. Another method for hiding the boar taint in meat products is addition of spices. Strong-smelling spices, such as paprika, chili, oregano, thyme, rosemary, mint, and cinnamon, can help to mask the stench of swine taint. Also, the use of essential oils in conjunction with spices and herbal extracts helps to mask the boar taint in meat products. Moreover, some of the recent publications focused on the investigation of yeast inoculation as a method for hiding boar taint.